The Influence of Sharia Financial Literacy on Islamic Bank Consumers’ Preference - Yayu Mulyawati; Rahmawati; Junaidi (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This research aims to determine the level of sharia financial literacy, awareness and attitudes of the community regarding their interest or decision to save at Sharia Banks. The data source for this research is the general public in Palopo City. The data analysis method used in this research is a quantitative method which is measured using Structural Equation Modeling (SEM). The statistical software programs used in analyzing the data were AMS 22 and SPSS 22. The awareness and attitudes have a significant influence on the decision to save in Islamic banks, but Islamic financial literacy does not have a significant influence on the decision to save in Islamic banks. Theoretically this research contributes to the literature review which has a correlation with sharia financial literacy, awareness and attitudes towards people's decisions to save in sharia banks. In practice, this research can help various parties, especially educators, from school to university and various related companies.